Water Leakage Detection for Complex Pipe Systems Using Hybrid Learning Algorithm Based on ANFIS Method - Yalcin, Baris Can; Demir, Cihan; Gokce, Murat; Koyun, Ahmet (ASME, 2018)
In most city water distribution systems, a considerable amount of water is lost because of leaks occurring in pipes. Moreover, an unobservable fluid leakage fault that may occur in a hazardous industrial system, such as nuclear power plant cooling process or chemical waste disposal, can cause both environmental and economical disasters. This situation generates crucial interest for industry and academia due to the . financial cost related with public health risks, environmental responsibility, and energy efficiency. In this paper, to find a reliable and economic solution for this problem, adaptive neuro fuzzy inference system (ANFIS) method which consists of backpropagation and least-squares learning algorithms is proposed for estimating leakage locations in a complex water distribution system. The hybrid algorithm is trained with acceleration, pressure, and flow rate data measured through the sensors located on some specific points of the complex water distribution system. The effectiveness of the proposed method is discussed comparing the results with the current methods popularly used in this area.
Keywords: DISTRIBUTION MODEL CALIBRATION; DIELECTRIC-SPECTROSCOPY; SAMPLING DESIGN; FUKUSHIMA; NETWORKS; REFLECTOMETRY; ACCIDENT; Computer Science; Engineering